Comparison of xenobiotic-metabolising human, porcine, rodent, and piscine cytochrome P450. (15th January 2017) - Burkina, Viktoriia; Rasmussen, Martin Krøyer; Pilipenko, Nadezhda; Zamaratskaia, Galia
Highlights: The percent identity of porcine, murine and piscine CYPs was compared with human CYPs. Main similarities and differences were reviewed. Understanding of molecular mechanisms of CYP system will provide further insights into the CYP regulatory processes, and responses to different factors. Abstract: Cytochrome P450 proteins (CYP450s) are present in most domains of life and play a critical role in the metabolism of endogenous compounds and xenobiotics. The effects of exposure to xenobiotics depend heavily on the expression and activity of drug-metabolizing CYP450s, which is determined by species, genetic background, age, gender, diet, and exposure to environmental pollutants. Numerous reports have investigated the role of different vertebrate CYP450s in xenobiotic metabolism. Model organisms provide powerful experimental tools to investigate Phase I metabolism. The aim of the present review is to compare the existing data on human CYP450 proteins (1–3 families) with those found in pigs, mice, and fish. We will highlight differences and similarities and identify research gaps which need to be addressed in order to use these species as models that mimic human traits. Moreover, we will discuss the roles of nuclear receptors in the cellular regulation of CYP450 expression in select organisms.